A normative study of the vestibulospinal and rotational tests. - Nyabenda A; Briart C; Deggouj N; Gersdorff M (Advances in Physiotherapy, 2004)
Vestibulospinal tests (static and dynamic conditions) and rotational tests are used for pre- and post-treatment evaluation of patients with peripheral vestibular balance disorders, but normative values remain yet unknown. The objective of this normative study is to determine, for different age groups, the normative values of vestibular rotational and vestibulospinal tests (static and dynamic conditions); to verify the effect of handedness on the direction of veering or rotation during dynamic testing; and to verify the effect of the veering or rotation direction on angle's amplitude. One hundred and twenty healthy volunteers aged from 20 to 79 years (without known balance or orthopedic disorders) underwent vestibulospinal tests (static and dynamic conditions) and rotational tests. The study included the Romberg, Unterberger-Fukuda and Babinski-Weil tests; gait testing eyes closed; and rotational testing using the rotational chair with and without optic fixation. Vestibulospinal and rotational test results increased significantly with age. We determined the normative values for each age group. The effect of handedness on the direction of the veering or rotation was not significant. The effect of the veering or rotation direction (left, right) on angle's amplitude was also not significant. For the entire study population and for each age group, we compared the required response time of stabilization for clockwise and counterclockwise rotational chair testing (with and without optic fixation): all differences were not significant. Age is an important factor in result of vestibulospinal and rotational tests. The handedness (left or right) does not influence vestibulospinal results. Thus, the outcome of pre- and post-treatment rotational tests and vestibulospinal tests (static and dynamic conditions) must be interpreted in function of the patient's age.